2005
DOI: 10.1111/j.1939-165x.2005.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the erythrocytes of cattle intoxicated withSeneciosp

Abstract: The results of this study indicate that poisoning by Senecio sp causes an increase in lipoperoxidation, oxidation of NPSH groups, and consequently, oxidative stress in bovine erythrocytes that may contribute to hemolysis. These findings may contribute to a better understanding of the mechanisms involved in cell damage in animals intoxicated by Senecio sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Sharma et al (1981) reported increased erythrocyte osmotic fragility in calves poisoned by lantana. Erythrocyte osmotic fragility increased due to lipid peroxidation and oxidative stress in cattle intoxicated with Senico sp (Bondan et al, 2005). Gossypol, a yellow polyphenolic compound, from whole cottonseed or cotton seed meal had been reported to increase the osmotic fragility of lactating cows (Mena et al, 2004), growing heifers (Colin-Negrete et al, 1996), cattle (Wyse et al, 1991), sheep and goats (Menges 1991;Matondi et al, 2007).…”
Section: Extracts Of Leaves Plants and Herbsmentioning
confidence: 99%
“…Sharma et al (1981) reported increased erythrocyte osmotic fragility in calves poisoned by lantana. Erythrocyte osmotic fragility increased due to lipid peroxidation and oxidative stress in cattle intoxicated with Senico sp (Bondan et al, 2005). Gossypol, a yellow polyphenolic compound, from whole cottonseed or cotton seed meal had been reported to increase the osmotic fragility of lactating cows (Mena et al, 2004), growing heifers (Colin-Negrete et al, 1996), cattle (Wyse et al, 1991), sheep and goats (Menges 1991;Matondi et al, 2007).…”
Section: Extracts Of Leaves Plants and Herbsmentioning
confidence: 99%
“…Pyrrolizidine alkaloids (PA), eremophilanolides and cacalolides are characteristic compounds isolated from Senecio species (13). Although the toxic effects exhibited by these plants have been largely attributed to their content of PA (14) the development of oxidative stress and the consequent generation of reactive oxygen species (ROS) and ROS-mediated cellular damage (15,16), likely also contribute to toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been evaluated in people in many different diseases including asthma, active and passive smoking, heart failure, renal failure, cancer, COPD, pulmonary hypertension, diabetes mellitus, ischemia and reperfusion injury, periodontal disease, blunt trauma, pneumonia, and ARDS . In large animals, changes in various biomarkers indicative of oxidative stress has been documented in a wide variety of conditions including recurrent airway obstruction in horses and various inflammatory diseases in cows and horses …”
Section: Inflammatory Respiratory Diseasementioning
confidence: 99%
“…306 In large animals, changes in various biomarkers indicative of oxidative stress has been documented in a wide variety of conditions including recurrent airway obstruction in horses and various inflammatory diseases in cows and horses. [307][308][309][310][311][312][313][314][315][316][317][318][319][320] There are several markers of oxidative stress that have been evaluated in dogs and cats in many different disease states, some of which are inflammatory in nature. [321][322][323][324][325][326][327][328][329][330][331][332][333][334][335][336][337] These include antioxidants such as vitamins A, C, and E; glutathione; cysteine; oxygen radical absorbance capacity; lipid peroxidation via malondialdehyde; oxidative damage to DNA; and elemental concentration of copper, selenium, zinc, magnesium, and iron.…”
Section: Oxidative Stressmentioning
confidence: 99%